PERANCANGAN VIDEO IKLAN UNTUK MENUNJANG PEMASARAN CLUB BOLA BASKET BIMASAKTI MALANG - Sugiarto, Jonathan Victor Abriliyan; Bakti, Amar Ma’aruf Stya; Nugroho, Didit Prasetyo (Ma Chung Press, Universitas Ma Chung, 2025)
The development of sports culture, particularly basketball, in Malang City has led to the emergence of many new basketball clubs, resulting in increasingly fierce competition. Bimasakti Malang Basketball Club, as one of the senior clubs, faces challenges to remain relevant and widely recognized by the public. This study aims to design a promotional advertisement video based on videography as an effective medium to reach target audiences and strengthen the club's image in an increasingly visual digital era. The method used in this design is a qualitative descriptive method, with data collection techniques including interviews, observations, documentation, and literature studies. The production process of the promotional video is carried out in three main stages: pre-production, production, and post-production, emphasizing cinematography, digital promotion strategies, and visual storytelling techniques. The target audience focuses on individuals aged 16–50 years, including both active sports enthusiasts and parents who are decision-makers for their children. The result of this design is a promotional advertisement video capable of attracting audience attention through social media, increasing engagement and interest in joining Bimasakti Club. This design also provides practical contributions to students, educational institutions, and the general public in understanding the importance of visual media in sports marketing strategies. Videography is proven to be not only a documentation tool but also a strategic communication tool that builds image, emotion, and connection with the audience more deeply.